Human Computer Interaction using gestures for mobile devices and serious games: A review sotirios spanogianopoulos - Sirlantzis, Konstantinos; Mentzelopoulos, Markos; Protopsaltis, Aristidis (Proceedings of 2014 International Conference on Interactive Mobile Communication Technologies and Learning, IMCL 2014, 2015)
The Human-Computer Interaction (HCI) with interfaces is an active challenge field in the industry over the past decades and has opened the way to communicate with the means of verbal, hand and body gestures using the latest technologies for a variety of different applications in areas such as video games, training and simulation. However, accurate recognition of gestures is still a challenge. In this paper, we review the basic principles and current methodologies used for collecting the raw gesture data from the user for recognize actions the users perform and the technologies currently used for gesture-HCI in games enterprise. In addition, we present a set of projects from various applications in games industry that are using gestural interaction.
Created from Fastlane, Scopus look-up
Keywords: Augmented Reality (AR); Gesture Recognition; HCI; Hidden Markov Models (HMM); Support Vector Machines (SVM)